A simple and quick way for diagnosis of erwinia amylova - (:unkn) unknown (International Society for Horticultural Science, 1999)
Since it was first detected in 1985, fireblight, caused by Erwinia amylovora, has been a disease of major importance in pome fruit growing regions of Turkey. Monoclonal antibodies (MAM iF 10) specific to E. amylovora were produced to identify and detect epiphytic and endophytic E. amylovora in pome fruit tissues by sandwich enzyme linked immunosorbent assay (ELISA). MAM1F1O was purified and conjugated to both alkaline phosphatase (AP) and horseradish peroxidase (HRPO). These two conjugates reacted positively in sandwich ELISA against pure cultures of 58 E. amylovora isolates originating from different hosts and geographical areas in Turkey. MAM1FIO was also tested against 17 unidentified epiphytic bacteria from apple, quince and pear trees collected from different provinces in Turkey.
Keywords: Erwinia amylovora; Immunodiagnosis; Monoclonal Antibody; Sandwich ELISA